2012
DOI: 10.1016/j.bbadis.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-histone lysine acetylated proteins in heart failure

Abstract: Both histone-acetylations and histone deacetylases have been shown to play a key role in cardiac remodeling. Recently, it has become abundantly clear that many non-histone proteins are modified by post-translational lysine acetylations and that these acetylations regulate protein activity, conformation, and binding. In the present study, non-histone acetylated proteins associated with heart failure were identified. Global screening for lysine acetylated proteins was performed using 2-dimensional gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…Our LC-MS/MS results demonstrate that GAPDH recruited upon iron loading lacks phosphorylation and acetylation and also has a lower abundance of several PTMs, including oxidation, dimethylation and nitrosylation in comparison to GAPDH recruited upon iron depletion. These modifications are well known for their ability to shift the isoelectric point of proteins as observed by us in this study, as well as by numerous other workers previously (Choudhary et al, 2000;Grillon et al, 2012;Kuyumcu-Martinez et al, 2007;Madian et al, 2012;Park et al, 1988;Zhang et al, 2011). The presence of numerous PTMs in GAPDH has been well established in earlier reports (Seidler, 2013;Seo et al, 2008).…”
Section: Discussionsupporting
confidence: 61%
“…Our LC-MS/MS results demonstrate that GAPDH recruited upon iron loading lacks phosphorylation and acetylation and also has a lower abundance of several PTMs, including oxidation, dimethylation and nitrosylation in comparison to GAPDH recruited upon iron depletion. These modifications are well known for their ability to shift the isoelectric point of proteins as observed by us in this study, as well as by numerous other workers previously (Choudhary et al, 2000;Grillon et al, 2012;Kuyumcu-Martinez et al, 2007;Madian et al, 2012;Park et al, 1988;Zhang et al, 2011). The presence of numerous PTMs in GAPDH has been well established in earlier reports (Seidler, 2013;Seo et al, 2008).…”
Section: Discussionsupporting
confidence: 61%
“…Impairment in mitochondrial energetics is a hallmark of the failing heart; the underlying mechanisms of which remain incompletely understood, but may include oxidative stress and impairment in mitochondrial biogenic signaling [12,30]. Recent studies showed that expression of SIRT3 is decreased in the failing rat heart, accompanied by increased acetylation of mitochondrial enzymes such as ATP synthase, long-chain acyl-CoA dehydrogenase, malate dehydrogenase, and pyruvate dehydrogenase [17,38]. In addition, activity of poly(adenosine diphosphate-ribose) polymerase 1 (PARP-1) is increased in the failing heart, whereas expression of nicotinamide phosphoribosyltransferase (Nampt) is decreased, both resulting in myocardial NAD ?…”
Section: Discussionmentioning
confidence: 98%
“…Thus, when extrapolating the metabolic and functional data of the current study and the data available from the literature, it is tempting to speculate that mitochondrial NAD ? depletion and/or decreased SIRT3 expression may impair SIRT3 activity and thereby contribute to impairment in mitochondrial energetics and contractile function in failing hearts [17,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…during decompensated hypertrophy and heart failure [45]. Indeed, lysine acetylation is increased in human failing hearts, even accompanied by reduced SIRT3 expression [45,46]. Another attractive hypothesis for decreased NAD ?…”
Section: Sirt3 In Cardiac Physiology and Diseasementioning
confidence: 99%